Mechanical properties, drying shrinkage, microstructure of modified cement mortar based on poly(acrylamide-co-methacrylic acid) microgel. (17th May 2021) - Zhang, Gengtong; Xia, Huiyun; Zhang, Wenshuo; Niu, Yanhui; Song, Lifang; Chen, Huaxin; Cao, Dongwei
Graphical abstract: Highlights: A novel kind of microgel has been synthesized by inverse suspension polymerization. The microgel showed a desired absorption and water retention in cement filtrate. The drying shrinkage and compressive strength of modified mortar were improved. Abstract: In this paper, three kinds of P(AM- co -MAA) microgels with different anion contents were synthesized by inverse suspension polymerization with acrylamide (AM) and methacrylic acid (MAA). The modified mortar was prepared by cement and sand as fillers and P(AM- co -MAA) as internal curing agent. The swelling behavior of P(AM- co -MAA) microgels with different anion contents in aqueous solutions was studied. The effects of P(AM- co -MAA) and commercial superabsorbent polymer (SAP) on the flowability, mechanical properties, drying shrinkage and microstructure of mortar were investigated. The results showed that the presence of multivalent cations (mainly Ca 2+ ) weakened the absorption capacity of microgels in cement filtrate. Spherical microgels had no negative effects on the flowability and mechanical properties of cementitious materials. The compressive strength of modified mortar can be significantly improved at later curing stage due to dome structure and internal curing. Furthermore, the water content of modified mortar with 0.1% additions of microgel decreased, and the drying shrinkage rate of the modified mortar was about 36% lower than that of cement mortar without microgels. It can also be observed that a large amount of macro pores were not formed around the microgels.